2019
DOI: 10.1212/wnl.0000000000008617
|View full text |Cite
|
Sign up to set email alerts
|

Disability worsening among persons with multiple sclerosis and depression

Abstract: ObjectiveDepression is common in multiple sclerosis (MS), but its impact on disability worsening has not yet been determined. We explored the risk of disability worsening associated with depression in a nationwide longitudinal cohort.MethodsThis retrospective cohort study used linked data from 3 Swedish nationwide registries: the MS Register, National Patient Register, and Prescribed Drug Register. Two incident cohorts were developed: cohort 1 included all registered cases of MS in the MS Registry (2001–2014) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 44 publications
2
47
0
Order By: Relevance
“…It is not always obvious which disease costs relate to, as some comorbidity is independent of MS and yet others may be a result of MS [ 64 ]. Furthermore, comorbidity may alter the MS clinical course, as observed with depression [ 65 ], and consequently further MS-specific healthcare may be needed. The reference group and use of excess costs also adjusted for aging and wider societal changes over time [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is not always obvious which disease costs relate to, as some comorbidity is independent of MS and yet others may be a result of MS [ 64 ]. Furthermore, comorbidity may alter the MS clinical course, as observed with depression [ 65 ], and consequently further MS-specific healthcare may be needed. The reference group and use of excess costs also adjusted for aging and wider societal changes over time [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the presence of depression was associated with a significantly higher subsequent disability over an average of 10 years of follow-up in women who constituted two-thirds of the investigated population ( 72 ). The impact of depression was also investigated in more than 15,000 patients from The Swedish MS registry, which found that MS patients with depression or bipolar disorder showed a significantly higher risk of progression on the Expanded Disability Status Scale (EDSS) score ( 73 ).…”
Section: Investigating Comorbidities In Populations With Msmentioning
confidence: 99%
“…The main consequence of depressive symptoms is scarce adherence to pharmacological treatments or rehabilitative programs associated to worsening of functional outcomes (Binzer et al, 2019). Although these symptoms represent one of the main determinants for quality of life in MS, they are currently undervalued and undertreated in clinical practice.…”
Section: Depressive Symptoms In Msmentioning
confidence: 99%